Pragmatic transfer in the speech act of refusals as produced by native speakers of Vietnamese in English : - Wa, Thái Như Phương (Can Tho University, 2008)
This study was intended to investigate pragmatic transfer from Vietnamese to English of Vietnamese learners of English as a foreign language (EFL) in order to enhance the effectiveness of EFL teaching and learning in Vietnam as well as teaching Vietnamese for the foreigners.